Agnes Grey’s Search for Self-Identity in Agnes Grey by Anne Bronte - Rahayuningsih, Yanti (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2019)
This study aims to reveal, identify and describe Agnes Grey's search for self-identity. Also, the writer of the thesis wants to show that the situations in Agnes Grey's adolescence period are the same as the real life of the author, Anne Bronte. The research method used is the psychology of literature. The results of the analysis indicated that by using theory from Erik H. Erikson, Agnes Grey found her true self in three stages. Key Words: self-identity, individuation, psychology approach.